The effect of level of teacher's expaectation and teacher's differential behavior on students' motivation. Percy Joy C. Supena. - Supena, Percy Joy C. (2004.)
This study investigated the effect of level of teacher's expectation and differential behavior on students motivation employing a 2x2 Factoral design. Sixty grade four students of San Miguel Central Elementary School were selected as participants. Motivation to learn in class was measured using a qustionnaire (replicated from Thorkildsen and Nicholls, 1998). Data gathered were analyzed using a two-way between groups analysis of variance with alpha level set at .05. The results showed that teacher's expectation and teacher's differential behavior had significant effect on student motivation and combination of teacher's expectation and differential behavior showed significance interaction.
Research Project (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, UP Visayas, Miagao, Iloilo
Keywords: Teachers